2020
DOI: 10.1177/0963689720949247
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Tripartite Motif 8 Protects H9C2 Cells Against Hypoxia/Reoxygenation-Induced Injury Through the Activation of PI3K/Akt Signaling Pathway

Abstract: Tripartite motif 8 (TRIM8) is a member of the TRIM protein family that has been found to be implicated in cardiovascular disease. However, the role of TRIM8 in myocardial ischemia/reperfusion (I/R) has not been investigated. We aimed to explore the effect of TRIM8 on cardiomyocyte H9c2 cells exposed to hypoxia/reoxygenation (H/R). We found that TRIM8 expression was markedly upregulated in H9c2 cells after stimulation with H/R. Gain- and loss-of-function assays proved that TRIM8 knockdown improved cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…It was reported that knockdown of TRIM8 suppressed H/R-generated oxidative stress and apoptosis in cardiac H9C2 cells, which was achieved through PI3K/Akt signaling pathway. 18 Notably, blockage of TRIM8 enhanced phosphorylation of PI3K/Akt in si-TRIM8 group versus si-NC group, which represented that PI3K/Akt signaling pathway was activated by TRIM8 inhibition ( Figure 5A and B ).
Figure 5 PI3K/Akt signaling pathway was involved in TRIM8 inhibition-regulated H/R injury in HK-2 cells.
…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It was reported that knockdown of TRIM8 suppressed H/R-generated oxidative stress and apoptosis in cardiac H9C2 cells, which was achieved through PI3K/Akt signaling pathway. 18 Notably, blockage of TRIM8 enhanced phosphorylation of PI3K/Akt in si-TRIM8 group versus si-NC group, which represented that PI3K/Akt signaling pathway was activated by TRIM8 inhibition ( Figure 5A and B ).
Figure 5 PI3K/Akt signaling pathway was involved in TRIM8 inhibition-regulated H/R injury in HK-2 cells.
…”
Section: Resultsmentioning
confidence: 90%
“… 16 Downregulation of TRIM8 was confirmed to mitigate damage by relieving oxidative stress and apoptosis in oxygen–glucose deprivation/re-oxygenation-induced injury in neurons, 17 as well as in H/R-induced injury in cardiac H9C2 cells. 18 The results suggested that the protective effect of TRIM8 inhibition in neurons was associated with reinforcement of the AMPK/Nrf2/ARE pathway, which was an important antioxidant pathway. In cardiac H9C2 cells, its protective effect was connected with the activation of PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, the Wnt signalling pathway is a classical neuron development signalling pathway [ 42 ]. Meanwhile, TRIM8 [ 43 ] and RPSA [ 44 ] are also an important regulators of the PI3K-AKT-mTOR signalling pathway, which is a developmental disease-related signalling pathway [ 40 ]. LHX2 is a regulator of neural differentiation [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, in H/R-stimulated H9c2 cells TRIM8 silencing causes a marked increase in Bcl-2 expression and the activation of the PI3K/Akt signaling pathway, which is well documented in being associated with a decrease in myocardial ischemic injury. PI3K/Akt activation inhibits cardiomyocyte apoptosis induced by hypoxia, and it protects against I/R injury [ 63 ].…”
Section: The Dark Side Of Trim8mentioning
confidence: 99%